1989
DOI: 10.2337/diab.38.6.691
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Insulin Secretory Patterns in Obese Nondiabetic LA/N-cp and Obese Diabetic SHR/N-cp Rats: Role of Hyperglycemia

Abstract: Obese diabetic SHR/N-(cp/cp) rats are a genetic model for non-insulin-dependent diabetes mellitus. When SHR/N-cp rats are overtly diabetic, they are hyperinsulinemic and hyperglycemic in the fed state when consuming commercial chow or semipurified high-carbohydrate diets. Obese SHR/N-cp rats were hyperinsulinemic by 4 wk of age, although hyperglycemia did not appear until 3-4 wk later and was exacerbated by a high-sucrose diet (mean +/- SE 1488 +/- 238 microU/ml insulin and 425 +/- 51 mg/dl glucose). The contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 13 publications
0
4
1
Order By: Relevance
“…The present data cannot entirely explain the differential effect of a 48-h hyperglycaemic period on the subsequent in vivo and in vitro insulin secretion that we and others reported previously [9,[18][19][20]. In particular, the in vivo insulin response to a low glucose concentration (8 mmol/1) was much higher in HG rats than in controls whereas this difference disappeared in vitro.…”
Section: Discussioncontrasting
confidence: 90%
“…The present data cannot entirely explain the differential effect of a 48-h hyperglycaemic period on the subsequent in vivo and in vitro insulin secretion that we and others reported previously [9,[18][19][20]. In particular, the in vivo insulin response to a low glucose concentration (8 mmol/1) was much higher in HG rats than in controls whereas this difference disappeared in vitro.…”
Section: Discussioncontrasting
confidence: 90%
“…The hyperinsulinemia can be exacerbated by a high-sucrose diet [105]. In 5-month old male rats, plasma insulin levels are 6 times higher than those of their lean controls [58].…”
Section: Introductionmentioning
confidence: 99%
“…Other investigators also concluded that a simple osmotic effect could not explain the massive hypersecretion in pancreas perfusions from glucose-infused rats (31). Third, nondiabetic genetically obese hyperinsulinemic rats (LA/N-cp/cp) also exhibit paradoxical secretion during pancreas perfusions (7) and in batch incubations of isolated islets (32), despite having normal blood glucose levels. Fourth, paradoxical hypersecretion appears to be inherently transient in isolated islets and wanes with time at 37°C, in either low or high Wanes with time at 37°C regardless of glucose (never seen in 2nd incubations) Partly mimicked by isolation of control islets in high glucose Partly reversed by isolation of infused islets in 0 glucose Persists after isolation in 0 glucose and lowglucose 1st incubation Most severe after continuous exposure of islets to high glucose Reversed by islet isolation in 0 glucose glucose.…”
Section: Discussionmentioning
confidence: 94%
“…Studies in our laboratory demonstrated that closely similar insulin secretory abnormalities were observed in perfused pancreases of genetically obese diabetic rats (SHR/N-cp [corpulent]) after 4 wk of hyperglycemia (6,7). However, when young hyperinsulinemic corpulent rats were studied before the development of hyperglycemia, the impaired insulin response to elevated glucose levels (desensitization) was not found (7), although the pancreases exhibited paradoxical secretion in low glucose.…”
mentioning
confidence: 76%
See 1 more Smart Citation